2008
DOI: 10.19030/rbis.v12i2.4384
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of End-User Training In Technology Acceptance

Abstract: The purpose of this paper is to examine the role end-user training has on performance expectancy and effort expectancy, two variables associated with technology acceptance. The technology-based elements of the HIPAA security rules among oral surgeons were used for the study. The method of the investigation was a cross-sectional correlational study using a self-reported mailed questionnaire. The survey was created using preexisting scales from the Unified Theory of Acceptance and Use of Technology. Results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Similarly, a study conducted by (Marshall, Mills, and Olsen 2008) in order to identify the effect of end-user training on the performance expectancy. The results reported that end-users' training about how to comply with the developed security policies has a positive relationship with the performance expectancy.…”
Section: Performance Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study conducted by (Marshall, Mills, and Olsen 2008) in order to identify the effect of end-user training on the performance expectancy. The results reported that end-users' training about how to comply with the developed security policies has a positive relationship with the performance expectancy.…”
Section: Performance Expectancymentioning
confidence: 99%
“…(Šumak, Polančič, and Heričko 2010) stated that performance expectancy directly affects behavioural intentions towards use of Moodle, but this study is biased towards students who have already technical skills for using the tool. (Engotoit et al 2016) Similarly, a study conducted by (Marshall, Mills, and Olsen 2008) in order to identify the effect of end-user training on the performance expectancy. The results reported that end-users' training about how to comply with the developed security policies has a positive relationship with the performance expectancy.…”
Section: Performance Expectancymentioning
confidence: 99%
“…A number of recent studies in a wide variety of research domains have applied the UTAUT model, including mobile banking implementations (Sangle and Awasthi, 2011;Zhou, 2012), wireless communications (Anderson and Schwager, 2004), organisational learning systems (Wong and Huang, 2011), and training in healthcare systems (Marshall et al, 2008). Figure 2 shows the hypothesised model used in this study.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…These studies have included an examination of organizational learning systems (Wong and Huang, 2011), mobile banking implementations (AbuShanab and Pearson, 2007;Zhou, 2012), 3G mobile communication (Mardikyan et al, 2012;Wu et al, 2012) and wireless communications (Anderson and Schwager, 2004). Furthermore, the UTAUT has been adopted as the theory to examine the acceptance by students of blackboard technology as indicated by Marchewka and Kostiwa (2014); Pynoo et al (2011) applied UTAUT to measure the level of acceptance and utilization of a digital learning environment by secondary school teachers, and UTAUT has been adopted as the theoretical framework to examine training in health care systems (Marshall et al, 2011).…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%